Red Hat certified engineer (RHCE) EX294. (Pearson, 2023)
9+ Hours of Video Instruction 9+ hours of video instruction and test-taking strategies for the 2023 RHCE exam. Red Hat Certified Engineer (RHCE) EX294, Second Edition provides more than 9 hours of video training to give you a solid understanding of the RHCE objectives. Experienced author and trainer Sander van Vugt covers all topics in the exam and ends each lesson with a lab walkthrough, so you can see how to complete goals and solve scenarios in real time. The course emphasizes how to perform common automation tasks using Ansible, as well as how to use common Ansible components to automate the management of a Linux environment. This video training was designed to provide an in-depth understanding of all topics on the Red Hat Certified Engineer (RHCE) exam, as well as a deeper understanding of Red Hat Enterprise Linux and Ansible. You will learn concepts, and then practice through video labs that you can also perform on your own so you can test your skills. Each lab ends with the instructor providing a detailed a solution where he explains how to solve for the exam objectives. Related Learning: Sign up for live training classes on RHCE and Ansible with Sander van Vugt: Red Hat Certified Engineer (RHCE) EX294 Crash Course: https://learning.oreilly.com/live-events/red-hat-certified-engineer-rhce-ex294-crash-course/0636920092161/ Ansible in 4 Hours: https://learning.oreilly.com/live-events/ansible-in-4-hours/0636920123842/ Topics included in this course: Introduction to Ansible is about the Ansible product offering, followed by lessons on how to set up an Ansible managed environment. After you've done that, you'll learn how to work with Ad Hoc commands, playbooks, as well as variables and facts. Using Advanced Ansible Solutions teaches the more advanced Ansible elements. The end of lesson labs will verify your Ansible knowledge by practicing how to apply task control, using loops, items, when, handlers, blocks, and more. Managing RHEL 9 with Ansible is about how to use Ansible for some common scenarios. It will cover scenarios about software management, user management, managing processes and tasks, managing storage, as well as networking. Sample Exam allows you to practice topics covered in the RHCE 9 objectives in a way that is very similar to what you'll see on the exam About the Instructor Sander van Vugt has many years of experience working with, writing about, and teaching Linux and Open-Source topics. He is the author of the best-selling Red Hat RHCSA and RHCE Cert Guides, as well as a number of other titles on Kubernetes (including CKAD and CKA), Ansible, Containers, Bash, Microservices, and more. Sander also works as a Linux and DevOps instructor, teaching onsite and online classes for customers around the world. Skill Level : Intermediate/Advanced Learn How To : Work with Ansible Best prepare for the RHCE EX294 Manage RHEL 9 with Ansible Set up a Managed IT Environment Use Ad Hoc Commands and Playbooks to manage RHEL 9 Servers Work with Ansible Content Collections Course requirement: Plan to, or have already, taken the RHCSA Exam A working knowledge of Linux Who Should Take This Course : Linux engineers that want to become certified to work with Ansible to manage Red Hat Enterprise Linux Junior system administrators that want to deepen their skills in configuration management Administrators with a profound knowledge and experience working with any Linux distributions, and want to learn how to use Ansible to manage their environment Administrators currently administering UNIX systems Developers that write software for Linux Administrators who have already completed the RHCSA Exam About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.